The Theory of Love - Laurie, Timothy. author. aut Link
VII, 87 p.
Keywords: “The Theory of Love offers a lucid, engaging, and thought-rich meditation on its topic. Adopting an affirmative though by no means uncritical stance, its authors explore how love is being reimagined in art, politics, and philosophy. What, they ask, might a post-sentimental idea of love look like?” — Rita Felski, William R. Kenan Jr., Professor of English at the University of Virginia, USA “The Theory of Love offers a fantastic tour of contemporary ideas about relationships covering the good, the bad, and the lovely. Offering love as a form of invention, this book proposes that it is less of a feeling than an orientation. Original and illuminating.” —Jack Halberstam, Professor of Gender and English at Columbia University, USA “Bringing together highly original cultural materials with diverse theories, the authors present readers with tools for creative worlding practices – a ‘becoming sensitive’ to realms outside our own frames of reference. This fine text is destined to become a touchtone for twenty-first century political praxis.” —Chantelle Gray, Associate Professor in the School of Philosophy, North-West University, South Africa The Theory of Love: Ideals, Limits, Futures explores stories about intimate life as a resource for creating bonds beyond heterosexual coupledom. The book offers a variety of ethical and imaginative frames through which to understand changing definitions of love, intimacy, and interdependency in the context of struggles for marriage equality and the increasing recognition of post-nuclear forms of kinship and care. In committing to these arrangements, it pushes beyond the false choice between a politics of collective action and the celebration of deeply personal and incommunicable pleasures. Exploring the vicissitudes of love across contemporary philosophy, politics, film, new media, and literature, The Theory of Love: Ideals, Limits, Futures argues for a post-sentimental understanding of the worlds that love is capable of making. Timothy Laurie is a Senior Lecturer in the School of Communication at the University of Technology Sydney, Australia. He is a Managing Editor of Continuum: Journal of Media & Cultural Studies and is co-editor of Unsettled Voices: Beyond Free Speech in the Late Liberal Era (2021). He is currently working on a collaborative project entitled ‘Australian Boys: Beyond the Boy Problem’ funded by the Australian Research Council. Hannah Stark is an Associate Professor in English at the University of Tasmania, Australia. She is the author of Feminist Theory After Deleuze (2016), and the co-editor of Deleuze and the Non/Human (2015) and Deleuze and Guattari in the Anthropocene (2016). She is currently working on a project funded by the Australian Research Council, ‘Beyond Extinction: Reconstructing the Thylacine (Tasmanian Tiger) Archive’. .